The benefits of nurturing care interventions on early child development and care: findings from a quasi-experimental study in a humanitarian setting - Viktoria Sargsyan; Ana Tenorio; Mediatrice Uwera; Andre Gasirikare; Jean Aime Habyarimana; Jennifer S Salcido; Christy Felner; Muneera A. Rasheed (BMC, 2023)
Abstract Background The study objective was to determine if a nurturing care parenting intervention delivered in a humanitarian setting in Rwanda would benefit early development, learning, and care outcomes for young children under five years and their caregivers compared to standard care. Methodology Rwanda's Mugombwa, Kansi, and Kigeme refugee camps and host communities implemented the parenting program. Via a quasi-experimental research design, the study assessed the effects of intervention delivered as a high dose (HD: 12 group sessions and four home visits) or low dose (LD: 6 group sessions and two home visits) on child and caregiver outcomes compared to the control group from similar settings receiving standard care. The Ages and Stages Questionnaires-3 (ASQ-3) assessed child development outcomes. The Multiple Indicator Cluster Survey questionnaire assessed parenting practices concerning early learning and stimulation. Findings The assessment included 733 children and families in total: HD = 314, LD = 240, control = 179. The researchers found no significant difference in child development scores between the intervention and control groups. Significantly higher proportion of caregivers exposed to HD and LD packages had engaged in early learning and stimulation practices compared to the control group, respectively, with 211(67.2%), 148 (61.7%) vs. 66 (36.9%), p < 0.001 caregivers engaged in 4 or more activities in the past three days. Similarly, on responsive feeding items, a higher percentage of HD and LD group caregivers were engaged in positive behaviours compared to the control group: 164 (52.2%), 108 (45%) vs. 62 (34.6%), p = 0.001. The study found no difference between the study arms regarding caregiver mental health. Conclusion Parenting programmes in humanitarian settings can improve nurturing care practices, even with a low dose, which is essential to strengthening children's resilience in at-risk conditions. Further studies in humanitarian contexts are crucial to understand the implementation needs in sensitive contexts.